2016
DOI: 10.1016/j.pop.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Statistics

Abstract: Obesity is a chronic disease that is strongly associated with an increase in mortality and morbidity including, certain types of cancer, cardiovascular disease, disability, diabetes mellitus, hypertension, osteoarthritis, and stroke. In adults, overweight is defined as a body mass index (BMI) of 25 kg/m(2) to 29 kg/m(2) and obesity as a BMI of greater than 30 kg/m(2). If current trends continue, it is estimated that, by the year 2030, 38% of the world's adult population will be overweight and another 20% obese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
330
0
24

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(357 citation statements)
references
References 73 publications
3
330
0
24
Order By: Relevance
“…Overweight and obesity are associated with chronic diseases that are frequently seen among CCSs, such as type 2 diabetes and cardiovascular disease (46,47). Poor diet and a sedentary lifestyle could further increase these already elevated risks.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Overweight and obesity are associated with chronic diseases that are frequently seen among CCSs, such as type 2 diabetes and cardiovascular disease (46,47). Poor diet and a sedentary lifestyle could further increase these already elevated risks.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Worldwide, obesity affects individuals of all ages and socioeconomic levels in both developed and developing countries including Turkey [1]. The prevalence and comorbidities of obesity are also increasing around the world.…”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that, 2.2 billion adults are overweight or obese worldwide. Moreover, estimations based on regression analysis , suggested that , by 2030 ,more than 20%of adults will be obese in addition to 38% will be overweight as well, if the current trends continue in the same manner [2,3]. Obesity as a chronic disease , is strongly associated with an increase in mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%